2018
DOI: 10.1186/s12920-018-0390-6
|View full text |Cite
|
Sign up to set email alerts
|

Rare variants in the splicing regulatory elements of EXOC3L4 are associated with brain glucose metabolism in Alzheimer’s disease

Abstract: BackgroundAlzheimer’s disease (AD) is one of the most common neurodegenerative diseases that causes problems related to brain function. To some extent it is understood on a molecular level how AD arises, however there are a lack of biomarkers that can be used for early diagnosis. Two popular methods to identify AD-related biomarkers use genetics and neuroimaging. Genes and neuroimaging phenotypes have provided some insights as to the potential for AD biomarkers. While the field of imaging-genomics has identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The cell death-associated protein kinase family (DAPK) may be therapeutic targets [ 98 ]. Variants in the splicing regulatory elements of EXOC3L4 were associated with Alzheimer’s disease [ 99 ]. GRID2 is important for the function of the NMDA receptor that plays a key role in synaptogenesis, synaptic plasticity, and motor coordination and that is a therapeutic target in AD [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cell death-associated protein kinase family (DAPK) may be therapeutic targets [ 98 ]. Variants in the splicing regulatory elements of EXOC3L4 were associated with Alzheimer’s disease [ 99 ]. GRID2 is important for the function of the NMDA receptor that plays a key role in synaptogenesis, synaptic plasticity, and motor coordination and that is a therapeutic target in AD [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…The peak marker for end body condition maps to Pachón scaffold KB872296.1. Based on analysis of coding sequences, we found that four genes on this scaffold exhibit evidence of non-neutral evolution and two of the four genes also have fixed differences between Pachón cavefish and both Río Choy and Rascón surface fish: ahnak2 (ENSAMXG00000001960) that is predicted to encode a nucleoprotein involved in calcium signaling, and exoc3l4 (ENSAMXG00000001944) that encodes an exocyst complex component associated with global cortical glucose metabolism in humans [18] (Additional file 3). The single ahnak2 gene in the Pachón genome is annotated as three separate genes in the surface fish genome.…”
Section: Traitmentioning
confidence: 99%
“…The cell death-associated protein kinase family (DAPK) may be therapeutic targets [93]. Variants in the splicing regulatory elements of EXOC3L4 were associated with Alzheimer's disease [94]. GRID2 is important for the function of the NMDA receptor that plays a key role in synaptogenesis, synaptic plasticity, and motor coordination and that is a therapeutic target in AD [95].…”
Section: Agreement With Previous Genetic and Biochemical Experimentsmentioning
confidence: 99%